INTEGRATING FOLKLORE INTO LITERACY INSTRUCTION TO PROMOTE STUDENTS' CULTURAL AWARENESS IN INDONESIAN SECONDARY SCHOOLS - Tina Sheba Cornelia Sitompul; Ulfah Sari Rezeki (SENSEI RESEARCH CENTER, 2024)
Cultural awareness is an essential component of literacy education because students need to understand texts not only as linguistic products but also as cultural expressions that contain values, identities, beliefs, and social meanings. However, literacy instruction in many classrooms still emphasizes decoding, vocabulary, literal comprehension, and written exercises, while students' local cultural knowledge is rarely used as a meaningful resource for reading and interpretation. This study aims to examine the effectiveness of integrating folklore into literacy instruction to promote students' cultural awareness and to explore how students experience folklore-based literacy activities. The study employed a mixed-method design using a quasi-experimental pretest-posttest control group approach supported by classroom observations, student interviews, reflective journals, and document analysis. The participants were 84 Grade VIII students divided into an experimental group and a control group. The experimental group received folklore-based literacy instruction through reading, cultural inquiry, narrative analysis, value reflection, group discussion, and creative response tasks. The control group received conventional literacy instruction using general narrative texts. Quantitative data were analyzed using descriptive statistics, paired-sample t-tests, independent-sample t-tests, normalized gain scores, and effect size analysis. Qualitative data were analyzed thematically. The findings showed that folklore-based literacy instruction significantly improved students' cultural awareness. Students developed stronger cultural knowledge, appreciation of local values, perspective-taking, and identity reflection. The study concludes that folklore can become a powerful literacy resource when cultural meanings are explicitly connected to reading, discussion, reflection, and student response.